Corruption and the impact of law enforcement: insights from a mixed-methods study in Malawi. Issue 3 (September 2020) - Anders, Gerhard; Kanyongolo, Fidelis E.; Seim, Brigitte
ABSTRACT: The article argues that the impact of law enforcement efforts against corruption deserves more scholarly attention. Drawing on a mixed-methods study from Malawi in southern Africa, where a large-scale law enforcement operation has been investigating and prosecuting those involved in a 2013 corruption scandal known as 'Cashgate', the article explores the potential for corruption deterrence from the perspective of government officials in the Malawi civil service. Malawi provides a challenging environment for deterrence due to limited state capacity, weak law enforcement agencies and widespread corruption. Nonetheless, the research findings show that Malawian government officials perceive prosecutions and convictions to deter corruption, both with regards to the law enforcement response to Cashgate specifically and law enforcement efforts in general. The findings from Malawi suggest that law enforcement and criminal justice have the potential to make an important contribution to anti-corruption strategies in Africa and the Global South at large.